2012
DOI: 10.1007/s10578-012-0290-5
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Parenting Practices and Parent Emotion Factors in Children at Risk for Disruptive Behavior Disorders

Abstract: The goal of this study was to examine the impact of different parenting characteristics on child disruptive behavior and emotional regulation among a sample of at-risk children. The sample consisted of 373 Australian 5- to 9-year-old children who were screened for serious behavior problems. Seven parenting variables based on self-report were evaluated, involving parenting practices, emotion beliefs and behaviors, emotion expressiveness, and mental health. Outcome variables based on parent/teacher report were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 42 publications
1
59
0
5
Order By: Relevance
“…The evaluation showed that mothers who attended TIK were significantly less emotion dismissing with a moderate effect size, a finding consistent with original studies of the TIK program in Australia [11,15]. Emotion dismissing parenting has been found to be detrimental to children's emotional and behavioral development [20], and so, reductions in this aspect of parenting are important. In contrast to community samples [15] and consistent with previous clinical evaluations [9,11] of TIK, in the current study, mothers did not report any increase in emotion coaching.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The evaluation showed that mothers who attended TIK were significantly less emotion dismissing with a moderate effect size, a finding consistent with original studies of the TIK program in Australia [11,15]. Emotion dismissing parenting has been found to be detrimental to children's emotional and behavioral development [20], and so, reductions in this aspect of parenting are important. In contrast to community samples [15] and consistent with previous clinical evaluations [9,11] of TIK, in the current study, mothers did not report any increase in emotion coaching.…”
Section: Discussionsupporting
confidence: 73%
“…According to the research literature, there is a link between emotion dismissive parenting and child disruptive behaviors [3,4,20,22]. While the TIK program is an emotion-focused intervention and used few behavioral strategies, mothers receiving TIK reported significant reductions in their children's behavior problems with a large effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Esto sugiere que el efecto de la falta de disciplina y el castigo corporal en la regulación de las emociones del niño puede ayudar a explicar por qué estas prácticas conducen a problemas serios de conducta en los niños y adolescentes (16).…”
Section: La Incoherencia En La Forma De Enseñarunclassified
“…However, children's long-term developmental outcomes are influenced by the extent to which their parents successfully manage their challenging behaviour (Shaw, Owens, Giovannelli, & Winslow, 2001). A number of parenting and family factors have been linked with the development of mental health issues and problems in children, including the lack of a warm, positive relationship with parents, lack of positive involvement and guidance, inflexible, inconsistent or overly harsh discipline, inadequate supervision and limit setting, and negative parental emotional expressiveness (e.g., Campbell, 1997;Duncombe et al, 2012;Stormshak, Bierman, McMahon, & Lengua, 2000). Other aspects related to the development of serious problem behaviour in children are socioeconomic disadvantage, parental mental health problems, criminal history, substance abuse and marital problems (e.g., Barry, Dunlap, Cotten, Lochman, & Wells, 2005;Malik et al, 2007;Webster-Stratton, 1990).…”
Section: The Role Of Parenting Practices In the Development Of Conducmentioning
confidence: 99%
“…Lack of a positive relationship with their parents and being exposed to dysfunctional, inconsistent parenting styles can have profound effects on a child's future (Duncombe, Havighurst, Holland, & Frankling, 2012;Scott, 2012). This thesis aspires to contribute to the goal of supporting parents in the most important job there is -raising the next generation.…”
Section: Introductionmentioning
confidence: 99%